PEMBUKAAN PRINSIP KERAHASIAAN BANK SEBAGAI PERBUATAN MELAWAN HUKUM (Studi Kasus Bank BCA) - Zatika, Dinda Anna (Faculty of Law, Universitas Pattimura, 2020)
Banking secrecy is known in many countries in the world that has a bank financial institution. Banking secrecy is one of the most important principle. It is because the development and growth of one bank is very dependant on public trust. Confidentiality of information that is born in banking activities, is needed for the benefit of the bank and also the interest of the customer itself. This research discussed about how is the function of the banking financial institution in protecting their customers through the banking secrecy and how is the form of tort of law against the banking secrecy in a judicial proceedings that linked to the case. Method used in this research is juridical normative research. Data are collected by literatures and documents studies, then analyzed using descriptive qualitative analysis. The results of this research indicate that to overcome problems with the banking secrecy, interference from the authorities in the consumer protection sector in the field of financial services is needed, that is Financial Services Authority institution or in Indonesian it is called Otoritas Jasa Keuangan. The institution is expected to be able to protect customers from financial service business that are considered to harm the interests of customers. In the case, the customer sued the bank for violation of banking secrecy on the basis of tort of law that is contrary to the bank’s legal obligations and the law as referred to the article 40 paragraph 1 of the Banking Law.